Alumina nanowire / rod and preparation method and application thereof
By using aluminum sources, alkaline compounds and bionic inducers in the preparation of alumina nanowires/rods, combined with aging and solvent heat treatment processes, the problem of difficult to prepare alumina nanowires/rods with high content of five-coordinated Al3+ defect positions and excellent length-to-diameter ratio in the prior art is solved, and an efficient and simple preparation method is achieved, which is convenient for industrial application.
Patent Information
- Application Number
- CN202311110703.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-08-31
AI Technical Summary
The prior art is difficult to efficiently and simply prepare alumina nanowires/rods with high content of five-coordinated Al3+ defect positions and excellent length-to-diameter ratio.
Alumina nanowires/rods were obtained by mixing the aluminum source, alkaline compounds, bionic inducers, regulators and solvents, and aging and solvent heat treatment. This method does not require additional template agents, catalysts or emulsifiers, simplifies the process flow and facilitates industrial production.
It has achieved efficient preparation of aluminum oxide nanowires/rods, with excellent aspect ratio and specific surface area, and at the same time, the content and proportion of five-coordinated Al3+ defective positions are increased. It is suitable for catalyst carriers, gas-liquid adsorption, solid-phase fillers and wastewater treatment agents.
Smart Images

Figure CN119551696A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum oxide, and in particular to an aluminum oxide nanowire / rod and a preparation method and application thereof. Background Art
[0002] At present, it is estimated that 85% of the global chemical industry involves catalytic processes, especially in the field of heterogeneous catalysis, which is a diverse and highly interdisciplinary field that combines materials and surface science, physics, analytical and theoretical chemistry, chemical engineering and other aspects, and is an important aspect of the entire catalytic process. Catalysts are the core of industrial catalytic processes, and catalyst carriers are one of the important factors affecting catalyst activity. At present, common carriers mainly include metal oxides, metal organic framework compounds (MOFs), molecular sieves, carbon materials and new materials. By rationally designing the carrier structure, such as introducing vacancies, doping and lattice defect structures, the catalytic performance can be effectively improved. For example, Zhang et al. found that small-grained ZrO2 catalysts have defect sites such as edges, corners, and step positions with a high exposure ratio. Under the same processing conditions, they are more likely to produce high concentrations of active Zr species, making the catalyst have a higher alkane activation ability (Nature Communications, 2018, 9, 3794). Therefore, the development of catalyst materials with specific morphological structures is a hot research direction to improve the efficiency of industrial processes.
[0003] One-dimensional nanomaterials, such as nanorods or nanowires, have attracted extensive attention in constructing optoelectronic, optical, and chemical sensing devices at the nanoscale. One-dimensional metal oxide materials retain a high specific surface area, show better thermal stability, and have excellent adsorption capacity for specific chemical or biological molecules. One-dimensional nanomaterials have been widely used to manufacture solid-state devices such as field-effect transistors, inverters, light-emitting diodes, sensors, and even simple memories.
[0004] Alumina is a typical acidic carrier, widely used in catalytic research and industrial applications. Changes in the physical and chemical properties of alumina will affect its interaction with metals, and thus affect the interaction between reactants and products. In recent years, with the development of preparation technology, nanostructured alumina has attracted widespread attention for its rich microscopic morphology and high catalytic performance. As a carrier, alumina can provide high thermal and hydrothermal stability for the catalyst, and different pore sizes and various specific structural exposure surfaces also provide a powerful place for the modification and modification of active metal species. Recent studies have found that nanostructured alumina with an unsaturated coordination structure (five-coordinated Al 3+ The presence of γ-alumina with high specific surface area and high five-coordinated Al2O3 has an important influence on the dispersion of metals and can improve the interaction between metals and carriers (Nanoscale, 2015, 7, 13313-13344).3+ Al2O3 nanowires with high defect site content are of great significance for the design of efficient industrial catalysts and the development of efficient and energy-saving chemical processes.
[0005] At present, the preparation of nanowire / rod alumina materials can be completed by special preparation methods, adjusting preparation parameters, and adding template agents. For example, CN111848140A and CN103991889A respectively achieve the preparation of alumina nanowires / rods by freeze drying and ball milling; CN103449491A and CN110512310A introduce emulsifiers or additives in the process of preparing alumina to achieve the preparation of alumina nanowires; CN109467110A, CN114394612A, CN102557092A and CN101880049A prepare nanorod / wire-shaped alumina materials by introducing template agents such as graphene and monosaccharides, but the template agent needs to be removed during the preparation process; CN101885501A uses metal Cu as a catalyst to complete the growth of alumina nanowires.
[0006] However, there are still few studies on the preparation of alumina nanowires / rods by simple and efficient methods, especially the efficient and simple preparation of alumina nanowires / rods with high content of pentacoordinated Al 3+ The preparation method of aluminum oxide nanowires / rods with defect sites, high aspect ratio and high specific surface area has not been reported yet. Summary of the invention
[0007] The purpose of the present invention is to overcome the above technical problems and provide an aluminum oxide nanowire / rod and a preparation method and application thereof, wherein the aluminum oxide nanowire / rod has excellent aspect ratio and specific surface area, and also has a high content and high proportion of penta-coordinated Al 3+ defective bits; at the same time, the method also simplifies the process flow and facilitates industrial production.
[0008] The first aspect of the present invention provides an aluminum oxide nanowire / rod, wherein the aspect ratio of the aluminum oxide nanowire / rod is ≥10 and the specific surface area is ≥200m 2 / g; the five-coordinated Al in the alumina nanowires / rods 3+ The content of defect sites is ≥1.95mmol / g, accounting for ≥10%.
[0009] In the present invention, unless otherwise specified, the aluminum oxide nanowires / rods include aluminum oxide nanowires and aluminum oxide nanorods.
[0010] In the present invention, the coordination of alumina includes: tetracoordination, pentacoordination and hexacoordination, that is, Al(VI), Al(V) and Al(IV). Among them, Al(VI) and Al(IV) are fully coordinated, that is, the Al atoms are occupied by O atoms; while Al(V) is special. In this case, the Al atom lacks an O coordination, that is, the Al atom still has a single electron that is not paired. Therefore, Al(V) can adsorb metals and participate in chemical reactions. This is why the preparation of alumina with a high content and high proportion of Al(V) is required.
[0011] Preferably, the surface of the aluminum oxide nanowires / rods has a convex structure.
[0012] Preferably, 27 In the Al solid nuclear magnetic resonance spectrum, the aluminum oxide nanowires / rods have characteristic peaks with chemical shifts at 7ppm±10%, 40ppm±10% and 77ppm±10%.
[0013] A second aspect of the present invention provides a method for preparing aluminum oxide nanowires / rods, the preparation method comprising:
[0014] (1) mixing an aluminum source, an alkaline compound, an optional biomimetic inducer, a regulator, and a solvent, and aging the obtained mixture to obtain an aging product containing aluminum oxide precursor seed crystals;
[0015] (2) subjecting the aged product to a solvent thermal treatment to obtain a solid-liquid mixture;
[0016] (3) separating the solid-liquid mixture into solid and liquid, and sequentially drying and calcining the obtained alumina precursor to obtain alumina nanowires / rods;
[0017] The conditions of the solvent thermal treatment include: temperature of 80-200°C; time of 4-72h.
[0018] The third aspect of the present invention provides an application of the alumina nanowires / rods provided in the first aspect, or the alumina nanowires / rods prepared by the preparation method provided in the second aspect, in catalyst carriers, gas-liquid adsorption, solid phase fillers and sewage treatment agents.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] (1) The alumina nanowires / rods provided by the present invention have an excellent aspect ratio and a high specific surface area, which effectively improves the pentacoordinated Al 3+ The content and proportion of defect sites; preferably, the aluminum oxide nanowires / rods also have a convex structure, so that the aluminum oxide nanowires / rods have a specific structural characteristic;
[0021] (2) The preparation method provided by the present invention directly uses aging and solvent thermal treatment on the mixture containing aluminum source to achieve the regulation of the density of special sites on the surface of aluminum oxide, specifically regulating the density of unsaturated coordinated aluminum species (five-coordinated Al 3+ The preparation method uses alkaline compounds and regulators to assist direct aging and solvent thermal treatment to achieve regulation of unsaturated coordinated aluminum species on the surface of alumina;
[0022] (3) The preparation method provided by the present invention also uses natural biological dried preparations as biomimetic inducers to form nanowire materials / rods with convex structures; at the same time, the preparation method does not require the addition of additional templates, catalysts or emulsifiers, simplifies the process flow, and is convenient for industrial production;
[0023] (4) The alumina nanowires / rods provided by the present invention have a high content of unsaturated aluminum species (five-coordinated Al 3+ ) density, and can be widely used in petrochemical and fine chemical industries, especially in the fields of catalyst carriers, gas-liquid adsorption, solid phase fillers and sewage treatment agents. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a SEM image of the aluminum oxide nanowire S1 prepared in Example 1;
[0025] Figure 2 is the XRD pattern of the aluminum oxide nanowire S1 prepared in Example 1;
[0026] Figure 3 is a N2 adsorption-desorption curve of the aluminum oxide nanowire S1 prepared in Example 1;
[0027] Figure 4 The aluminum oxide nanowire S1 prepared in Example 1 27 Al solid NMR spectrum;
[0028] Figure 5 is a SEM image of the aluminum oxide nanowire S2 prepared in Example 2;
[0029] Figure 6 is a SEM image of aluminum oxide DS1 prepared in Comparative Example 1;
[0030] Figure 7 is the commercial alumina DS3 in Comparative Example 3 27 Al solid NMR spectrum. DETAILED DESCRIPTION
[0031] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0032] The first aspect of the present invention provides an aluminum oxide nanowire / rod, wherein the aspect ratio of the aluminum oxide nanowire / rod is ≥10 and the specific surface area is ≥200m 2 / g; the five-coordinated Al in the alumina nanowire 3+ The content of defect sites is ≥1.95mmol / g, accounting for ≥10%.
[0033] The inventors of this application have found that the structure of the surface of alumina is complex. The microstructure of the surface makes alumina have a variety of applications in the field of fine chemicals, while the density of a specific structure will also limit its application in a specific field. Therefore, by regulating the density of special sites on the surface of alumina, especially regulating the unsaturated coordinated aluminum species (five-coordinated Al 3+ The density of defect sites) was effectively improved under the premise of ensuring that the alumina nanowires have excellent aspect ratio and high specific surface area. 3+ The content of defect sites makes the pentacoordinated Al 3+ The content of defect sites is ≥1.95mmol / g, accounting for ≥10%.
[0034] Preferably, during the preparation of alumina nanowires / rods, a natural biological desiccant with a superhydrophobic structure is added as a bionic inducer, such as the nanosheet structure on canna leaves or the nanowires on the surface of ramie leaves, etc. The special surface structure of natural organisms can be used to effectively induce the alumina nanowires / rods to form a specific structure, that is, a spherical convex structure is formed on the surface of the alumina nanowires / rods.
[0035] In the present invention, unless otherwise specified, the pentacoordinated Al 3+ The content of defective sites is based on 27 The calculation is based on the Al solid nuclear magnetic resonance spectrum, that is, the aluminum species in the alumina material are divided into three types, namely, the aluminum species structures with chemical shifts near 7, 40 and 77 ppm, which belong to Al(VI), Al(V) and Al(IV), respectively. According to the ratio of the peak areas of the three, the molar fraction of the unsaturated coordinated aluminum species (Al(V)) is determined, that is, the proportion Based on the above molar fraction, the molar fraction of Al(V) is multiplied by twice the molar number of aluminum oxide in 1g of aluminum oxide nanowires / rods, which is converted into the molar content of Al(V) = x(Al(V))×2×0.0098, where 0.0098 is the molar number of Al2O3 in 1g. The molar number of alumina is the sum of the moles of aluminum species of Al(VI), Al(V) and Al(IV).
[0036] In some embodiments of the present invention, preferably, the aspect ratio of the aluminum oxide nanowires / rods is 10-1000, for example, 10, 20, 50, 80, 100, 200, 300, 500, 1000, and any value in the range of any two values, preferably 10-300; the specific surface area is 200-500m 2 / g, for example, 200m 2 / g, 220m 2 / g, 250m 2 / g, 280m 2 / g、300m 2 / g、500m 2 / g, and any value in the range of any two values, preferably 200-300m 2 In the present invention, the specific surface area parameter is measured by a fully automatic isothermal adsorption instrument.
[0037] In a specific embodiment of the present invention, when the aspect ratio is 10, the nano-alumina has a rod-like structure, that is, an alumina nanorod; when the aspect ratio is greater than 10, the nano-alumina has a wire-like structure, that is, an alumina nanowire.
[0038] In some embodiments of the present invention, preferably, the five-coordinated Al 3+ The defect content is 1.95-5.9mmol / g, for example, 2mmol / g, 2.5mmol / g, 3mmol / g, 3.5mmol / g, 4mmol / g, 4.5mmol / g, 5mmol / g, 5.5mmol / g, 5.9mmol / g, and any value in the range of any two values, preferably 2.9-4.9mmol / g; the proportion is 10-30%, for example, 10%, 15%, 18%, 20%, 22%, 25%, 30%, and any value in the range of any two values, preferably 15-25%. In the present invention, the alumina nanowires / rods that meet the above range are more conducive to improving the adsorption activity and catalytic activity of unsaturated coordinated aluminum species.
[0039] In some embodiments of the present invention, preferably, the length of the aluminum oxide nanowires / rods is 10 nm-500 μm, preferably 100 nm-300 μm.
[0040] In the present invention, the alumina nanowires / rods have a mesoporous structure. Preferably, the pore volume of the alumina nanowires / rods is 0.1-5 cm 3 / g, preferably 0.2-3cm 3 / g; the average pore diameter is 5-100nm, preferably 10-60nm. In the present invention, the average pore diameter parameter and the pore volume parameter are measured by a fully automatic isothermal adsorption instrument and calculated in conjunction with the BJH model.
[0041] In some embodiments of the present invention, preferably, Figure 1 As shown, the surface of the aluminum oxide nanowires / rods has a convex structure.
[0042] In some embodiments of the present invention, further preferably, the diameter of the convex structure is 1-100 nm, preferably 1-60 nm; the coverage of the convex structure is ≤30%, preferably 5-30%. In the present invention, the coverage refers to the proportion of the convex structure on the surface of the aluminum oxide nanowire / rod.
[0043] In some embodiments of the present invention, preferably, the aluminum oxide nanowires / rods have an amorphous crystalline phase structure. In the present invention, the crystalline phase parameters are obtained by X-ray powder diffraction analysis; and the microscopic morphology parameters are measured by scanning electron microscopy.
[0044] In some embodiments of the present invention, preferably, 27 In the Al solid nuclear magnetic resonance spectrum, the aluminum oxide nanowires / rods have characteristic peaks with chemical shifts at 7ppm±10%, 40ppm±10% and 77ppm±10%, which are respectively attributed to the aluminum species structures of Al(VI), Al(V) and Al(IV).
[0045] A second aspect of the present invention provides a method for preparing aluminum oxide nanowires / rods, the preparation method comprising:
[0046] (1) mixing an aluminum source, an alkaline compound, an optional biomimetic inducer, a regulator, and a solvent, and aging the obtained mixture to obtain an aging product containing aluminum oxide precursor seed crystals;
[0047] (2) subjecting the aged product to a solvent thermal treatment to obtain a solid-liquid mixture;
[0048] (3) separating the solid-liquid mixture into solid and liquid, and sequentially drying and calcining the obtained alumina precursor to obtain alumina nanowires / rods;
[0049] The conditions of the solvent thermal treatment include: temperature of 80-200°C; time of 4-72h.
[0050] In the preparation method provided by the present invention, an alkaline compound (preferably urea) is used as a precipitant, which is slowly hydrolyzed during solvent thermal treatment to form a base to promote the formation of aluminum oxide. The conditions of the solvent thermal treatment and the amount of the alkaline compound are combined to regulate the crystallization rate of the aluminum precursor, thereby achieving the formation of nanowire / rod-shaped aluminum oxide. At the same time, a regulating agent is added to allow specific adsorption during the solvent thermal treatment (crystallization process), thereby guiding the formation of aluminum oxide and forming a specific nanowire / rod morphology.
[0051] In some embodiments of the present invention, preferably, in step (1), the molar ratio of the alkaline compound to the aluminum source in terms of Al is 4-100:1, for example, 4:1, 5:1, 8:1, 10:1, 15:1, 20:1, 30:1, 50:1, 100:1, and any value in the range of any two values, preferably 4-20:1. In the present invention, when the molar ratio is lower than 4:1, the amount of the alkaline compound is too small, which is not conducive to the precipitation of aluminum oxide; when the molar ratio is higher than 100:1, the amount of the alkaline compound is too large, and the precipitation rate in the crystallization is too large, which is not conducive to the formation of nano-morphology aluminum oxide.
[0052] In some embodiments of the present invention, preferably, in step (1), the mass ratio of the aluminum source, the alkaline compound, the bionic inducer and the regulator is 1-20:1-35:0-0.5:0.001-1, preferably 2-10:3-10:0.001-0.1:0.01-1.
[0053] In some embodiments of the present invention, preferably, the ratio of the aluminum source in g to the solvent in mL is 1-20:35-200, preferably 2-10:60-90.
[0054] In the present invention, the feed amount / dosage ratio of the aluminum source, alkaline compound, biomimetic inducer, regulator and solvent only needs to meet the above-mentioned definition.
[0055] In the present invention, the mixing conditions have a wide range of selection, as long as the above components are mixed. Preferably, the mixing conditions include: temperature of 0-50°C, preferably 20-35°C; rotation speed of 0-1000rpm, preferably 200-500rpm; time of 0.5-5h, preferably 0.5-2h.
[0056] In the present invention, the type of the aluminum source has a wide selection range. Preferably, the aluminum source is a soluble aluminum salt, including but not limited to aluminum nitrate, aluminum chloride, aluminum acetylacetonate, aluminum acetate, etc.
[0057] In the present invention, the type of the alkaline compound has a wide selection range. Preferably, the alkaline compound is selected from inorganic bases and / or organic bases, preferably at least one selected from ammonia water, urea, sodium hydroxide and tetrapropylammonium hydroxide, more preferably urea.
[0058] In a specific embodiment of the present invention, the concentration of aqueous ammonia is 25 wt %, and the concentration of tetrapropylammonium hydroxide solution is 25 wt %.
[0059] In the present invention, the types of the bionic inducer have a wide selection range. Preferably, the bionic inducer is selected from natural biological dry preparations, and the natural organism is selected from at least one of watermelon rind, lotus leaf, rice leaf and ramie leaf.
[0060] In a specific embodiment of the present invention, when the bionic inducer is selected from two natural dry preparations, and the natural organisms are selected from two of watermelon rind, lotus leaf, rice leaf and ramie leaf, the present invention does not limit the mass ratio of the two natural dry preparations.
[0061] In the present invention, a natural biological desiccant with a superhydrophobic structure is added as a bionic inducer, such as a nanosheet structure on a canna leaf or a nanowire on the surface of a ramie leaf, etc., and the special surface structure of natural organisms is utilized to effectively induce the aluminum oxide nanowires / rods to form a specific structure, that is, a spherical convex structure is formed on the aluminum oxide nanowires / rods.
[0062] In the present invention, the type of the control agent has a wide selection range. Preferably, the control agent is selected from ammonium compounds, preferably at least one selected from ammonium carbonate, ammonium bicarbonate, ammonium sulfate and ammonium oxalate.
[0063] In the present invention, the type of the solvent has a wide range of choices. Preferably, the solvent is selected from at least one of water, methanol, ethanol, toluene, N,N-dimethylformamide, etc.; more preferably, the solvent is water.
[0064] In the present invention, in step (1), the aging is intended to convert aluminum ions in the mixture into aluminum oxide precursor seeds. Preferably, the aging conditions include: a temperature of 0-100°C, preferably 30-80°C; and a time of 0.5-24h, preferably 0.5-5h.
[0065] In the present invention, the solvent thermal treatment is intended to further grow the alumina precursor seed crystals through a dissolution-crystallization process in a hydrothermal environment. Controlling the solvent thermal conditions can obtain products with specific morphologies. Without solvent thermal treatment, the seed crystals cannot participate in the dissolution-crystallization process and cannot form a specific morphology.
[0066] In some embodiments of the present invention, further preferably, the solvent thermal treatment conditions include 100-150° C. and time of 12-48 h.
[0067] In some embodiments of the present invention, the drying is intended to remove the residual solvent in the alumina precursor. Preferably, in step (3), the drying conditions include: a temperature of 80-150°C, preferably 90-110°C; and a time of 5-72h, preferably 12-24h.
[0068] In the present invention, the drying method has a wide range of choices. Preferably, the drying method includes but is not limited to spray drying, blast drying, vacuum drying, etc.
[0069] In some embodiments of the present invention, preferably, in step (3), the calcination conditions include: a temperature of 300-1000°C, preferably 400-600°C; a time of 1-8h, preferably 3-5h. In the present invention, the calcination is carried out in a muffle furnace or a tubular furnace, and the calcination atmosphere is a non-reducing gas, preferably at least one of air, nitrogen and argon.
[0070] In some embodiments of the present invention, preferably, the method further comprises: before the drying, filtering and washing the alumina precursor in sequence.
[0071] In the present invention, the suction filtration and washing are intended to remove the residual alkaline compounds and regulators in the alumina precursor. Preferably, the device used for the suction filtration includes but is not limited to a water pump, a diaphragm pump, a diffusion pump, and the like.
[0072] In some embodiments of the present invention, preferably, the washing process comprises: contacting the filtered product with a washing liquid and washing. The washing liquid used for the washing has a wide selection range, preferably, the washing liquid is selected from water and / or C1-C5 monohydric alcohol, and the C1-C5 monohydric alcohol includes but is not limited to methanol, ethanol, 1-pentanol, etc.
[0073] The third aspect of the present invention provides an application of the alumina nanowires / rods provided in the first aspect, or the alumina nanowires / rods prepared by the method provided in the second aspect, in catalyst carriers, gas-liquid adsorption, solid phase fillers and sewage treatment agents.
[0074] In the present invention, the high specific surface area and high five-coordinated Al are conducive to the adsorption of more substances in the adsorption reaction; as a catalyst carrier, more and more stable metals can be loaded; as a catalyst, due to the presence of unsaturated coordinated Al, more reaction sites can be provided for the reaction, thereby improving the reaction efficiency.
[0075] According to a particularly preferred embodiment of the present invention, an aluminum oxide nanowire / rod, wherein the aspect ratio of the aluminum oxide nanowire / rod is 10-300, the specific surface area is 200-300m 2 / g; the five-coordinated Al in the alumina nanowires / rods 3 + The content of defect sites is 1.95-5.9mmol / g, accounting for 10-30%;
[0076] The above-mentioned aluminum oxide nanowires / rods are prepared by the following method: (1) mixing an aluminum source, an alkaline compound, an optional bionic inducer, a regulator and a solvent, and aging the obtained mixture to obtain an aging product containing aluminum oxide precursor seed crystals; (2) subjecting the aging product to solvent thermal treatment to obtain a solid-liquid mixture; (3) subjecting the solid-liquid mixture to solid-liquid separation, and the obtained aluminum oxide precursor is dried and calcined in sequence to obtain aluminum oxide nanowires / rods;
[0077] Among them, the conditions of the solvent thermal treatment include: temperature of 80-200°C; time of 4-72h; the molar ratio of the alkaline compound to the aluminum source calculated as Al is 4-100:1; the inducing release agent is selected from natural biological dry preparations, and the natural organism is selected from at least one of watermelon peel, lotus leaf, rice leaf and ramie leaf.
[0078] The present invention will be described in detail below through examples.
[0079] The physical properties of the products obtained in Examples 1-15 and Comparative Examples 1-4 are listed in Table 1.
[0080] Example 1
[0081] (1) 4.5 g of an aluminum source (aluminum nitrate nonahydrate), 6.5 g of an alkaline compound (urea), 0.1 g of a biomimetic inducer (dried watermelon rind and dried lotus leaf in a mass ratio of 1:1), 0.05 g of a regulator (ammonium carbonate) and 60 mL of a solvent (water) were mixed (temperature: 10° C., rotation speed: 600 rpm, time: 5 h), and the obtained mixture was aged at 30° C. for 4 h to obtain an aged product containing aluminum oxide precursor seed crystals;
[0082] The molar ratio of the alkaline compound to the aluminum source in terms of Al is 9:1;
[0083] (2) The aged product was transferred into a 200 mL hydrothermal reactor and subjected to solvent thermal treatment at 120 °C for 48 h to obtain a solid-liquid mixture;
[0084] (3) The solid-liquid mixture is subjected to solid-liquid separation, and the obtained alumina precursor is filtered and washed with isopropanol in sequence. The washed product is dried in a blast drying oven at 120° C. for 8 h, and calcined in a muffle furnace at 550° C. for 4 h in static air to obtain alumina nanowires S1.
[0085] The SEM image of the aluminum oxide nanowire S1 is as follows: Figure 1 As shown by Figure 1 It can be seen that the aluminum oxide nanowire S1 presents a nanowire-like structure and has a convex structure.
[0086] The XRD pattern of the aluminum oxide nanowire S1 is as follows: Figure 2 As shown by Figure 2 It can be seen that the aluminum oxide nanowire S1 presents an amorphous crystal phase structure.
[0087] Among them, the N2 adsorption and desorption curve of the above-mentioned aluminum oxide nanowire S1 is as follows Figure 3 As shown by Figure 3 It can be seen that the aluminum oxide nanowire S1 has a mesoporous structure, and the reason for the formation of the mesoporous structure is presumed to be the stacked mesopores formed by the stacking of nanowire materials.
[0088] Among them, the aluminum oxide nanowire S1 27 Al solid NMR spectrum Figure 4 As shown by Figure 4 It can be seen that the characteristic peaks at chemical shifts of 7, 40 and 77 ppm are attributed to Al(VI), Al(V) and Al(IV) structures, respectively. 3+ The proportion of defect sites reached 12%, and the specific content was 2.35mmol / g.
[0089] Example 2
[0090] (1) 4.5 g of an aluminum source (aluminum nitrate nonahydrate), 6.5 g of an alkaline compound (urea), 0.01 g of a regulator (ammonium carbonate), and 60 mL of a solvent (water) were mixed (temperature: 30° C., rotation speed: 500 rpm, time: 2 h), and the resulting mixture was aged at 30° C. for 4 h to obtain an aged product containing aluminum oxide precursor seed crystals;
[0091] The molar ratio of the alkaline compound to the aluminum source in terms of Al is 9:1;
[0092] (2) The aged product was transferred into a 200 mL hydrothermal reactor and subjected to solvent thermal treatment at 100 °C for 48 h to obtain a solid-liquid mixture;
[0093] (3) The solid-liquid mixture is subjected to solid-liquid separation, and the obtained alumina precursor is filtered and washed with ethanol in sequence. The washed product is dried in a forced air drying oven at 110° C. for 12 h, and calcined in a muffle furnace at 550° C. for 4 h in static air to obtain alumina nanowires S2.
[0094] The SEM image of the aluminum oxide nanowire S2 is as follows: Figure 5 As shown by Figure 5 It can be seen that the aluminum oxide nanowire S2 presents a nanowire structure and has an excellent aspect ratio.
[0095] Among them, the XRD pattern of the above-mentioned aluminum oxide nanowire S2 is Figure 2 Similar; the N2 adsorption and desorption curve of the above-mentioned aluminum oxide nanowire S2 is Figure 3 Similar; the above aluminum oxide nanowire S2 27 Al solid NMR spectrum and Figure 4 similar.
[0096] Example 3
[0097] (1) 4.5 g of an aluminum source (aluminum nitrate nonahydrate), 6.5 g of an alkaline compound (urea), 0.01 g of a biomimetic inducer (dried lotus leaf), 0.01 g of a regulator (ammonium bicarbonate) and 60 mL of a solvent (water) were mixed (temperature: 0° C., rotation speed: 1000 rpm, time: 2 h), and the obtained mixture was aged at 30° C. for 4 h to obtain an aged product containing aluminum oxide precursor seed crystals;
[0098] The molar ratio of the alkaline compound to the aluminum source in terms of Al is 9:1;
[0099] (2) The aged product was transferred into a 200 mL hydrothermal reactor and subjected to solvent thermal treatment at 80 °C for 48 h to obtain a solid-liquid mixture;
[0100] (3) The solid-liquid mixture is subjected to solid-liquid separation, and the obtained alumina precursor is filtered and washed with 1-pentanol in sequence. The washed product is dried in a blast drying oven at 100° C. for 12 h, and calcined in a muffle furnace at 400° C. for 6 h in static air to obtain alumina nanowires S3.
[0101] Example 4
[0102] (1) 5 g of an aluminum source (aluminum chloride), 12.5 g of an alkaline compound (25 wt% ammonia water), 0.03 g of a biomimetic inducer (dried rice leaves), 0.02 g of a regulator (ammonium oxalate) and 35 mL of a solvent (methanol) were mixed (temperature: 20° C., rotation speed: 600 rpm, time: 4 h), and the obtained mixture was aged at 20° C. for 4 h to obtain an aged product containing aluminum oxide precursor seed crystals;
[0103] The molar ratio of the alkaline compound to the aluminum source in terms of Al is 4.9:1;
[0104] (2) The aged product was transferred into a 200 mL hydrothermal reactor and subjected to solvent thermal treatment at 140 °C for 48 h to obtain a solid-liquid mixture;
[0105] (3) The solid-liquid mixture is subjected to solid-liquid separation, and the obtained alumina precursor is filtered and washed with 1-pentanol in sequence. The washed product is dried in a forced air drying oven at 100° C. for 12 h, and calcined in a muffle furnace at 600° C. for 2 h in static air to obtain alumina nanowires S4.
[0106] Example 5
[0107] (1) 3 g of an aluminum source (aluminum acetylacetonate), 22 g of an alkaline compound (NaOH), 0.001 g of a biomimetic inducer (dried ramie leaves), 0.5 g of a regulator (ammonium sulfate) and 100 mL of a solvent (toluene) were mixed (temperature: 15° C., rotation speed: 800 rpm, time: 3 h), and the obtained mixture was aged at 50° C. for 5 h to obtain an aged product containing aluminum oxide precursor seed crystals;
[0108] The molar ratio of the alkaline compound to the aluminum source in terms of Al is 59.5:1;
[0109] (2) The aged product was transferred into a 200 mL hydrothermal reactor and subjected to solvent thermal treatment at 200 °C for 12 h to obtain a solid-liquid mixture;
[0110] (3) The solid-liquid mixture is subjected to solid-liquid separation, and the obtained alumina precursor is filtered and washed with ethanol in sequence. The washed product is dried in a forced air drying oven at 80° C. for 30 h, and calcined in a muffle furnace at 800° C. for 3 h in static air to obtain alumina nanowires S5.
[0111] Example 6
[0112] (1) 5 g of an aluminum source (aluminum acetate), 100 g of an alkaline compound (a 25 wt % tetrapropylammonium hydroxide solution), 0.007 g of a biomimetic inducer (dried watermelon rind), 0.8 g of a regulator (ammonium carbonate) and 95 mL of a solvent (ethanol) were mixed (temperature: 5° C., rotation speed: 500 rpm, time: 2 h), and the obtained mixture was aged at 80° C. for 2 h to obtain an aged product containing aluminum oxide precursor seed crystals;
[0113] The molar ratio of the alkaline compound to the aluminum source in terms of Al is 5:1;
[0114] (2) The aged product was transferred to a 300 mL hydrothermal reactor and subjected to solvent thermal treatment at 100 °C for 48 h to obtain a solid-liquid mixture;
[0115] (3) The solid-liquid mixture is subjected to solid-liquid separation, and the obtained alumina precursor is filtered and washed with ethanol in sequence. The washed product is dried in a blast drying oven at 100° C. for 20 h, and calcined in a muffle furnace at 500° C. for 5 h in static air to obtain alumina nanowires S6.
[0116] Example 7
[0117] (1) 10 g of an aluminum source (aluminum nitrate), 40 g of an alkaline compound (25 wt % ammonia water), 0.06 g of a biomimetic inducer (dried rice leaves and dried lotus leaves in a mass ratio of 1:1), 0.01 g of a regulator (ammonium bicarbonate) and 100 mL of a solvent (methanol) were mixed (temperature: 0° C., rotation speed: 600 rpm, time: 4 h), and the obtained mixture was aged at 60° C. for 5 h to obtain an aged product containing aluminum oxide precursor seed crystals;
[0118] The molar ratio of the alkaline compound to the aluminum source in terms of Al is 22:1;
[0119] (2) The aged product was transferred into a 200 mL hydrothermal reactor and subjected to solvent thermal treatment at 80 °C for 72 h to obtain a solid-liquid mixture;
[0120] (3) The solid-liquid mixture is subjected to solid-liquid separation, and the obtained alumina precursor is filtered and washed with ethanol in sequence. The washed product is dried in a blast drying oven at 120° C. for 10 h, and calcined in a muffle furnace at 600° C. for 2 h in static air to obtain alumina nanowires S7.
[0121] Example 8
[0122] (1) 7.5 g of an aluminum source (aluminum chloride), 32.5 g of an alkaline compound (25 wt % ammonia water), 0.01 g of a biomimetic inducer (dried ramie leaves and dried lotus leaves in a mass ratio of 1:1), 0.05 g of a regulator (ammonium sulfate) and 90 mL of a solvent (water) were mixed (temperature 45° C., rotation speed 800 rpm, time 2 h), and the resulting mixture was aged at 30° C. for 3 h to obtain an aged product containing aluminum oxide precursor seed crystals;
[0123] The molar ratio of the alkaline compound to the aluminum source in terms of Al is 8.5:1;
[0124] (2) The aged product was transferred into a 200 mL hydrothermal reactor and subjected to solvent thermal treatment at 200 °C for 12 h to obtain a solid-liquid mixture;
[0125] (3) The solid-liquid mixture is subjected to solid-liquid separation, and the obtained alumina precursor is filtered and washed with ethanol in sequence. The washed product is dried in a forced air drying oven at 150° C. for 5 h, and calcined in a muffle furnace at 600° C. for 2 h in static air to obtain alumina nanowires S8.
[0126] Example 9
[0127] (1) 4 g of an aluminum source (aluminum chloride), 10 g of an alkaline compound (aqueous ammonia with a concentration of 25 wt%), 0.07 g of a bionic inducer (dried watermelon rind and dried rice leaves in a mass ratio of 1:1), 0.1 g of a regulator (ammonium bicarbonate) and 95 mL of a solvent (toluene) were mixed (temperature of 50° C., rotation speed of 800 rpm, time of 3 h), and the obtained mixture was aged at 50° C. for 5 h to obtain an aged product containing aluminum oxide precursor seed crystals;
[0128] The molar ratio of the alkaline compound to the aluminum source in terms of Al is 4.9:1;
[0129] (2) The aged product was transferred into a 200 mL hydrothermal reactor and subjected to solvent thermal treatment at 150 °C for 24 h to obtain a solid-liquid mixture;
[0130] (3) The solid-liquid mixture is subjected to solid-liquid separation, and the obtained alumina precursor is filtered and washed with ethanol in sequence. The washed product is dried in a forced air drying oven at 110° C. for 20 h, and calcined in a muffle furnace at 400° C. for 4 h in static air to obtain alumina nanowires S9.
[0131] Example 10
[0132] (1) 5 g of an aluminum source (aluminum acetylacetonate), 15 g of an alkaline compound (NaOH), 0.005 g of a biomimetic inducer (dried watermelon rind), 0.1 g of a regulator (ammonium bicarbonate) and 100 mL of a solvent (methanol) were mixed (temperature: 30° C., rotation speed: 600 rpm, time: 2 h), and the obtained mixture was aged at 60° C. for 12 h to obtain an aged product containing aluminum oxide precursor seed crystals;
[0133] The molar ratio of the alkaline compound to the aluminum source in terms of Al is 24.3:1;
[0134] (2) The aged product was transferred into a 200 mL hydrothermal reactor and subjected to solvent thermal treatment at 120 °C for 12 h to obtain a solid-liquid mixture;
[0135] (3) The solid-liquid mixture is subjected to solid-liquid separation, and the obtained alumina precursor is filtered and washed with ethanol in sequence. The washed product is dried in a blast drying oven at 80° C. for 24 h, and calcined in a muffle furnace at 550° C. for 4 h in static air to obtain alumina nanowires S10.
[0136] Embodiment 11
[0137] (1) 2 g of an aluminum source (aluminum acetylacetonate), 40 g of an alkaline compound (25 wt % ammonia water), 0.02 g of a biomimetic inducer (dried watermelon rind), 0.02 g of a regulator (ammonium bicarbonate) and 60 mL of a solvent (water) were mixed (temperature: 30° C., rotation speed: 900 rpm, time: 0.5 h), and the obtained mixture was aged at 30° C. for 24 h to obtain an aged product containing aluminum oxide precursor seed crystals;
[0138] The molar ratio of the alkaline compound to the aluminum source in terms of Al is 95.4:1;
[0139] (2) The aged product was transferred into a 200 mL hydrothermal reactor and subjected to solvent thermal treatment at 160 °C for 72 h to obtain a solid-liquid mixture;
[0140] (3) The solid-liquid mixture is subjected to solid-liquid separation, and the obtained alumina precursor is filtered and washed with ethanol in sequence. The washed product is dried in a blast drying oven at 60° C. for 30 h, and calcined in a muffle furnace at 400° C. for 6 h in static air to obtain alumina nanowires S11.
[0141] Example 12
[0142] (1) 5 g of an aluminum source (aluminum acetate), 95 g of an alkaline compound (tetrapropylammonium hydroxide at a concentration of 25 wt%), 0.1 g of a biomimetic inducer (dried watermelon rind), 0.2 g of a regulator (ammonium sulfate) and 100 mL of a solvent (N,N-dimethylformamide) were mixed (temperature 50° C., rotation speed 900 rpm, time 0.5 h), and the resulting mixture was aged at 40° C. for 6 h to obtain an aged product containing aluminum oxide precursor seed crystals;
[0143] The molar ratio of the alkaline compound to the aluminum source in terms of Al is 4.8:1;
[0144] (2) The aged product was transferred into a 300 mL hydrothermal reactor and subjected to solvent thermal treatment at 150 °C for 60 h to obtain a solid-liquid mixture;
[0145] (3) The solid-liquid mixture is subjected to solid-liquid separation, and the obtained alumina precursor is filtered and washed with isopropanol in sequence. The washed product is dried in a blast drying oven at 150° C. for 10 h, and calcined in a muffle furnace at 550° C. for 6 h in static air to obtain alumina nanowires S12.
[0146] Embodiment 13
[0147] (1) 5 g of an aluminum source (aluminum acetate), 125 g of an alkaline compound (tetrapropylammonium hydroxide at a concentration of 25 wt%), 0.09 g of a biomimetic inducer (dried watermelon rind), 0.02 g of a regulator (ammonium sulfate) and 70 mL of a solvent (methanol) were mixed (temperature: 0° C., rotation speed: 500 rpm, time: 3 h), and the obtained mixture was aged at 30° C. for 12 h to obtain an aged product containing aluminum oxide precursor seed crystals;
[0148] The molar ratio of the alkaline compound to the aluminum source in terms of Al is 6.3:1;
[0149] (2) The aged product was transferred into a 300 mL hydrothermal reactor and subjected to solvent thermal treatment at 200 °C for 48 h to obtain a solid-liquid mixture;
[0150] (3) The solid-liquid mixture is subjected to solid-liquid separation, and the obtained alumina precursor is filtered and washed with isopropanol in sequence. The washed product is dried in a blast drying oven at 120° C. for 6 h, and calcined in a muffle furnace at 550° C. for 4 h in static air to obtain alumina nanowires S13.
[0151] Embodiment 14
[0152] (1) 4.5 g of an aluminum source (aluminum nitrate), 5.5 g of an alkaline compound (NaOH), 0.002 g of a biomimetic inducer (dried watermelon rind), 0.05 g of a regulator (ammonium oxalate), and 50 mL of a solvent (water) were mixed (temperature: 10° C., rotation speed: 700 rpm, time: 1 h), and the obtained mixture was aged at 30° C. for 12 h to obtain an aged product containing aluminum oxide precursor seed crystals;
[0153] The molar ratio of the alkaline compound to the aluminum source in terms of Al is 11.5:1;
[0154] (2) The aged product was transferred into a 100 mL hydrothermal reactor and subjected to solvent thermal treatment at 100 °C for 60 h to obtain a solid-liquid mixture;
[0155] (3) The solid-liquid mixture is subjected to solid-liquid separation, and the obtained alumina precursor is filtered and washed with isopropanol in sequence. The washed product is dried in a blast drying oven at 100° C. for 9 h, and calcined in a muffle furnace at 500° C. for 6 h in static air to obtain alumina nanowires S14.
[0156] Embodiment 15
[0157] (1) 4.5 g of an aluminum source (aluminum nitrate), 45 g of an alkaline compound (25 wt % ammonia water), 0.05 g of a biomimetic inducer (dried watermelon rind), 0.02 g of a regulator (ammonium carbonate) and 200 mL of a solvent (water) were mixed (temperature: 10° C., rotation speed: 700 rpm, time: 1 h), and the obtained mixture was aged at 30° C. for 8 h to obtain an aged product containing aluminum oxide precursor seed crystals;
[0158] The molar ratio of the alkaline compound to the aluminum source in terms of Al is 55.2:1;
[0159] (2) The aged product was transferred into a 300 mL hydrothermal reactor and subjected to solvent thermal treatment at 200 °C for 12 h to obtain a solid-liquid mixture;
[0160] (3) The solid-liquid mixture is subjected to solid-liquid separation, and the obtained alumina precursor is filtered and washed with isopropanol in sequence. The washed product is dried in a blast drying oven at 60° C. for 15 h, and calcined in a muffle furnace at 450° C. for 8 h in static air to obtain alumina nanowires S15.
[0161] Comparative Example 1
[0162] According to the method of Example 2, the difference is that
[0163] In step (1), the amount of the alkaline compound (urea) is replaced with 2.2 g, the amount of the regulating agent (ammonium carbonate) is replaced with 0.1 g, the molar ratio of the alkaline compound to the aluminum source calculated as Al is 3.1:1, and the other conditions are the same to obtain alumina DS1.
[0164] Among them, the SEM image of the above-mentioned aluminum oxide DS1 is as follows Figure 6 As shown by Figure 6 It can be seen that the aluminum oxide DS1 does not have a nanowire structure but a bulk aluminum oxide structure.
[0165] Comparative Example 2
[0166] According to the method of Example 2, the difference is that
[0167] In step (2), the temperature of the solvent thermal treatment is replaced with 60°C, which is the same as the conditions to obtain alumina DS2.
[0168] Comparative Example 3
[0169] Commercial alumina (Sinopharm Chemical Reagent Co., Ltd., CAS No.: 1344-28-1, Batch No.: 20170401) was used as alumina DS3.
[0170] Among them, the above aluminum oxide DS3 27 Al solid NMR spectrum Figure 7As shown by Figure 7 It can be seen that there is no characteristic peak at 40 ppm, indicating that the above aluminum oxide DS3 does not have a penta-coordinated Al 3+ , that is, Al(V) structure.
[0171] Comparative Example 4
[0172] According to the method of Example 1, the difference is that
[0173] In step (2), the aged product is directly heated at 100° C. for 48 h, with other conditions being the same, to obtain alumina DS4.
[0174] Table 1
[0175]
[0176]
[0177] Table 1
[0178]
[0179] It can be seen from the data in Table 1 that compared with Comparative Examples 1-4, the aluminum oxide nanowires prepared by the method provided by the present invention in Examples 1-15 have a high content and a high proportion of pentacoordinated Al under the premise of having a high aspect ratio and a high specific surface area. 3+ Defective bit.
[0180] Meanwhile, compared with Example 2, due to the addition of bionic inducers, the aluminum oxide nanowires prepared in Examples 1 and 3-15 not only have a nanowire structure but also a convex structure, and the diameter of the convex structure is 3-55 nm and the coverage is 5-28%.
[0181] Test Case
[0182] The alumina nanowires prepared in Examples 1-2 and the commercial alumina of Comparative Example 3 were used as carriers to load gallium (Ga) species. 3+ structure, which can effectively realize the anchoring of Ga species.
[0183] The preparation method includes: mixing 0.0227g of gallium nitrate, 0.6g of the above-mentioned carrier, and 10mL of water, stirring at 25°C for 4h and drying at 110°C for 24h; the dried sample is calcined in air at 550°C for 5h to obtain Ga-based alumina nanowire catalyst Ga / Al2O3-NW-1, Ga-based alumina nanowire catalyst Ga / Al2O3-NW-2, and Ga-based commercial alumina catalyst Ga / Al2O3-Comm, respectively.
[0184] The catalysts prepared as above were used in the propane oxygen-free dehydrogenation reaction. The specific reaction conditions were as follows: feed ratio C3H8:N2=2:3, propane gas rate of 8 mL / min, nitrogen gas rate of 12 mL / min, catalyst dosage of 50 mg, heating rate of 10°C / min, reaction temperature of 600°C. The test results are shown in Table 2.
[0185] Table 2
[0186] catalyst Propane conversion, % Propylene selectivity, % Example 1 <![CDATA[Ga / Al2O3-NW-1]]> 9.4 89.7 Example 2 <![CDATA[Ga / Al2O3-NW-2]]> 10 84.6 Comparative Example 3 <![CDATA[Ga / Al2O3-Comm]]> 5.6 56.0
[0187] It can be seen from the data in Table 2 that, compared with Comparative Example 3, the catalyst prepared by using the aluminum oxide nanowires provided by the present invention as a carrier and used in the propane oxygen-free dehydrogenation reaction has a higher propane conversion rate and propylene selectivity.
[0188] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An aluminum oxide nanowire / rod, characterized in that: The aspect ratio of the alumina nanowire / rod is ≥10, and the specific surface area is ≥200m 2 / g; the five-coordinated Al in the alumina nanowires / rods 3+ The content of defect sites is ≥1.95mmol / g, accounting for ≥10%.
2. The aluminum oxide nanowires / rods according to claim 1, wherein: The aspect ratio of the alumina nanowires / rods is 10-1000, preferably 10-300; the specific surface area is 200-500m 2 / g, preferably 200-300m 2 / g; And / or, the five-coordinated Al in the alumina nanowires / rods 3+ The content of defect sites is 1.95-5.9 mmol / g, preferably 2.9-4.9 mmol / g; the proportion is 10-30%, preferably 15-25%.
3. The aluminum oxide nanowires / rods according to claim 1 or 2, wherein: The length of the aluminum oxide nanowires / rods is 10 nm-500 μm, preferably 100 nm-300 μm; And / or, the pore volume of the alumina nanowires / rods is 0.1-5 cm 3 / g, preferably 0.2-3cm 3 / g; the average pore size is 5-100nm, preferably 10-60nm.
4. The aluminum oxide nanowire / rod according to any one of claims 1 to 3, wherein: The surface of the aluminum oxide nanowire / rod has a convex structure; Preferably, the diameter of the convex structure is 1-100 nm, preferably 1-60 nm; Preferably, the coverage of the convex structures is ≤30%, preferably 5-30%.
5. The aluminum oxide nanowire / rod according to any one of claims 1 to 4, wherein: The aluminum oxide nanowires / rods have an amorphous crystalline phase structure; and / or, in 27 In the Al solid nuclear magnetic resonance spectrum, the aluminum oxide nanowires / rods have characteristic peaks with chemical shifts at 7ppm±10%, 40ppm±10% and 77ppm±10%.
6. A method for preparing aluminum oxide nanowires / rods, characterized in that: The preparation method comprises: (1) mixing an aluminum source, an alkaline compound, an optional biomimetic inducer, a regulator, and a solvent, and aging the obtained mixture to obtain an aging product containing aluminum oxide precursor seed crystals; (2) subjecting the aged product to a solvent thermal treatment to obtain a solid-liquid mixture; (3) separating the solid-liquid mixture into solid and liquid, and sequentially drying and calcining the obtained alumina precursor to obtain alumina nanowires / rods; The conditions of the solvent thermal treatment include: temperature of 80-200°C; time of 4-72h.
7. The preparation method according to claim 6, wherein: In step (1), The molar ratio of the basic compound to the aluminum source calculated as Al is 4-100:1, preferably 4-20:1; And / or, the mass ratio of the aluminum source, the alkaline compound, the bionic inducer and the regulator is 1-20: 1-35: 0-0.5: 0.001-1, preferably 2-10: 3-10: 0.001-0.1: 0.01-1; and / or, the ratio of the aluminum source in g to the solvent in mL is 1-20:35-200, preferably 2-10:60-90; And / or, the aging conditions include: a temperature of 0-100°C, preferably 30-80°C; The time is 0.5-24h, preferably 0.5-5h.
8. The preparation method according to claim 6 or 7, wherein: In step (1), The alkaline compound is selected from inorganic bases and / or organic bases, preferably at least one selected from ammonia water, urea, sodium hydroxide and tetrapropylammonium hydroxide; And / or, the bionic inducer is selected from natural biological dried preparations, and the natural organism is selected from at least one of watermelon rind, lotus leaf, rice leaf and ramie leaf; And / or, the regulating agent is selected from ammonium compounds, preferably at least one selected from ammonium carbonate, ammonium bicarbonate, ammonium sulfate and ammonium oxalate.
9. The preparation method according to any one of claims 6 to 8, wherein: In step (2), the conditions of the solvent thermal treatment include: temperature of 100-150° C.; time of 12-48 h; And / or, in step (3), the drying conditions include: temperature of 80-150° C., preferably 90-110° C.; time of 5-72 h, preferably 12-24 h; And / or, the calcination conditions include: temperature of 300-1000°C, preferably 400-600°C; time of 1-8h, preferably 3-5h; And / or, the calcination is performed in a non-reducing gas.
10. Use of the alumina nanowires / rods according to any one of claims 1 to 5, or the alumina nanowires / rods prepared by the preparation method according to any one of claims 6 to 9, in catalyst carriers, gas-liquid adsorption, solid phase fillers and sewage treatment agents.
Citation Information
Patent Citations
Fast preparation method for coralloid nano alpha-Al2O3
CN101264913A
Preparation method of one-dimensional alumina nanowire / nano rod
CN101885501A
An alumina material, its preparation method and its application
CN102275963A
Method for preparing nano-alumina carrier with defect-rich surface
CN107824172A
Alumina and preparation method thereof, and catalyst loaded with noble metal
CN115504492A